E-COMMERCE DAN KEPERCAYAAN KONSUMEN: TINJAUAN LITERATUR SISTEMATIS TERHADAP TREN TERBARU DAN DAMPAKNYA PADA NIAT PEMBELIAN - Muhammad Imam Baihaqi; Laillyus Nur Fadhila; Riyan Sisiawan Putra; Martha Laila Arisanda; Aries Widya Gunawan (Fakultas Ekonomi Universitas Islam Darul Ulum Lamongan, 2025)
The development of e-commerce has brought significant changes in the way consumers shop, and one of the main factors that influence buyer decisions is the level of consumer trust in the digital platform. This study aims to provide a systematic review of the literature on the relationship between e-commerce and consumer trust, focusing on recent trends and their impact on purchase value. Based on the analysis of various relevant studies, it was found that factors such as transactions, quality of service, information transparency, and user reviews have a significant influence on consumer trust. In addition, technological developments such as the use of AI, digital payments, and personalization also play an important role in increasing consumer confidence in e-commerce platforms that can increase purchase intent, which ultimately contributes to the success of e-commerce businesses. It is hoped that these findings can provide insight for e-commerce practitioners in designing effective strategies to build consumer trust and increase sales.